2006
DOI: 10.3892/or.15.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human breast tumor-derived endothelial cells

Abstract: Abstract. Increasing evidence indicates that tumor-derived endothelial cells (TEC) possess a distinct and unique phenotype in respect to normal endothelial cells and may be able to acquire resistance to drugs. However, few functional studies are available on cultured TEC. In the present study, we obtained TEC from human breast carcinomas and, to dispel the possibility of contaminating tumor cells, we established six different clones that we characterized at a functional level. Breast TEC cell lines and clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 20 publications
4
66
2
Order By: Relevance
“…A similar surface expression profile was detected in mammary-derived TECs (mTECs) (data not shown). As extensively documented, TECs also differ from their normal counterpart for a rapid turnover rate in absence of growth factors (Bussolati et al, 2003;Grange et al, 2006). Indeed, monitoring rTEC and mTEC growth at low serum concentration (2%) for different time intervals (24, 48 and 72 h), an increase in cells in the S phase ( Figure 1b, upper panel) could be detected and this increased proliferative rate (Figure 1b, lower panel) was maintained for several passages (12 passages, data not shown).…”
Section: Tec Characterization and Functional Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…A similar surface expression profile was detected in mammary-derived TECs (mTECs) (data not shown). As extensively documented, TECs also differ from their normal counterpart for a rapid turnover rate in absence of growth factors (Bussolati et al, 2003;Grange et al, 2006). Indeed, monitoring rTEC and mTEC growth at low serum concentration (2%) for different time intervals (24, 48 and 72 h), an increase in cells in the S phase ( Figure 1b, upper panel) could be detected and this increased proliferative rate (Figure 1b, lower panel) was maintained for several passages (12 passages, data not shown).…”
Section: Tec Characterization and Functional Behaviormentioning
confidence: 98%
“…Thus, TECs, isolated from renal clear cell carcinomas and breast carcinomas by CD105-positive immunomagnetic sorting (Bussolati et al, 2003;Grange et al, 2006), were first analyzed for endothelial cell surface markers by cytofluorimetric analysis. As reported in Figure 1a, we found that renal TECs (rTECs) were positive for the expression of several endothelial cell markers, such as CD105, CD146 (c) Cell migration assay was performed in Boyden's chambers, as described in Materials and methods section.…”
Section: Tec Characterization and Functional Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…ECs were isolated, using anti-CD105 antibody coupled to magnetic beads, by magnetic cell sorting using the MACS system (Miltenyi Biotec) and grown in complete EBM (Cambrex) supplemented with 10% FCS (Cambrex), 50 μg/mL gentamicin (Cambrex), and 2 mmol/L glutamine (Cambrex) as previously described (10). Cells were used at passages 3 to 15.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Interestingly, TECs display a distinct and unique phenotype different from that of normal vascular ECs at molecular and functional levels (9)(10)(11). Recently, TECs obtained from breast carcinomas (B-TEC) have been established and characterized, showing an immature proangiogenic phenotype with enhanced proliferation, motility, and capillary-like tube formation compared with "normal" ECs (10,12).…”
Section: Introductionmentioning
confidence: 99%